2022
DOI: 10.1590/0001-3765202220200940
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and technological potential of Umbu (Spondias tuberosa Arr. Cam.) processing by-product flour

Abstract: Antioxidants present in many fruit residues can play an essential role in the prevention of diseases. The aim of this study was to determine nutritional and mineral composition, fatty acids profile, anti-nutrients, bioactive compounds, antioxidant activity and technological properties of flour from residues generated by umbu fruit processing. Nutritional composition showed high levels of dietary fiber, especially insoluble fiber (56.67%). The flour can be classified as a good source of calcium, phosphorus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 61 publications
4
4
4
Order By: Relevance
“…López-Camacho et al ( 2021) evaluated the yellow mombin seed oil describing a concentration-dependent antioxidant activity, with a maximum ABTS radical inhibition of 45%. Another study with Brazil plum residues showed similar elimination of ABTS and DPPH to that reported in the present study (Xavier et al, 2022).…”
Section: In Vitro Antioxidant Activitysupporting
confidence: 91%
See 4 more Smart Citations
“…López-Camacho et al ( 2021) evaluated the yellow mombin seed oil describing a concentration-dependent antioxidant activity, with a maximum ABTS radical inhibition of 45%. Another study with Brazil plum residues showed similar elimination of ABTS and DPPH to that reported in the present study (Xavier et al, 2022).…”
Section: In Vitro Antioxidant Activitysupporting
confidence: 91%
“…Emulsifying capacity is related to surface properties, the ability of a substance to act as an agent that facilitates the solubilization or dispersion of two immiscible liquids. The values found herein were lower than the results described by Xavier et al (2022) with Brazil plum residues.…”
Section: Solvent Tpc (Mg Gae/g) Ymf Bpfcontrasting
confidence: 89%
See 3 more Smart Citations